Dampak Kekerasan Orangtua Terhadap Perkembangan Kognitif Anak Usia 5-6 Tahun di Tk Al-Faruqi Tahun 2024/2025 (Penelitian Studi Kasus Di Tk Al-Faruqi Kecamatan Maniis Kabupaten Purwakarta) - Agni Herlin Apisah; Miftachul Jannah; Shalihat NurFitriyah.S (Jurnal Ilmu Pendidikan dan Sosial, 2024)
This study aims to examine the impact of parental violence on the cognitive development of children aged 5-6 years at TK Al-Faruqi. A qualitative research method was employed to gain a deep understanding of the experiences of children who have been subjected to violence and its effects on their cognitive development. In-depth interviews were conducted with three informants, including two classroom teachers and one parent, to identify various forms of violence, both physical and verbal. The findings indicate that physical violence, such as hitting, pinching, and slapping, frequently occurs within the context of parenting and significantly contributes to disruptions in the child’s thinking and problem-solving abilities. The effects of this physical violence include fear, stress, and learning difficulties, making it harder for children to grasp the material taught in school. On the other hand, verbal violence, such as yelling and using harsh language, can harm the child’s mental health and hinder the development of their self-confidence. Children who experience verbal abuse exhibit difficulties in concentrating and retaining information, negatively impacting their academic performance. Further analysis identified several factors that trigger parental violence, including unstable economic conditions and the inability of parents to manage their emotions. The informants revealed that economic pressure, especially during times of financial hardship, often leads to frustration that manifests as violence toward the child. Emotional mismanagement is also a significant reason behind violent behavior, despite parents being aware of its negative consequences. It was found that children who endure violence tend to experience learning delays, difficulties in social interaction, and deviant behavior. This study suggests the need for parental education on the negative effects of violence, as well as training in emotional and stress management. Such efforts are expected to prevent child abuse and create a safe, supportive, and conducive environment for optimal cognitive development.